Mitos Kelas Menengah ke Atas dalam Desain Iklan Politik Risma-Bambang - Bahruddin, Muh. (Nirmana, 2012)
Local elections (pilkada) in the entire territory of Indonesia affect the huge presence of the candidate's political advertising. This study examines myths about the middle to upper class in political advertising design of Risma-Bambang who won the mayoral election of Surabaya in 2010. This advertising design is interesting to study because it has a different concept of political advertising in general (out of the mainstream). The other candidate's political advertising design accentuate the face image in attracting potential voters in contras to political advertising design of Risma- Bambang that shous just a lot of display symbols that are accompanied with the tagline "Not The Others". Using a semiotic analysis from Roland Barthes, the results of this study indicate that in order to create the myth of middle to upper class in Surabaya, political advertising of Risma-Bambang has been labeled with the symbols of sandal slippers, penguin, and reading a book. This myth is known after doing an analysis of the paradigmatic, syntagmatic, denotation, and connotation in political advertising design of Risma-Bambang. The myth of the middle to upper class is imaged with intelligence, relaxing, and fun through these symbols.